Diversity Under Threat: Connecting Genetic Diversity and Threat Mapping to Set Conservation Priorities for Juglans regia L. Populations in Central Asia - Gaisberger, Hannes; Legay, Sylvain; Andre, Christelle; Loo, Judy; Azimov, Rashid; Aaliev, Sagynbek; Bobokalonov, Farhod; Mukhsimov, Nurullo; Kettle, Chris; Vinceti, Barbara (Frontiers in Ecology and Evolution, 2020)
Central Asia is an important center of diversity for common walnut (Juglans regia L.). We characterized the genetic diversity of 21 wild and cultivated populations across Kyrgyzstan, Tajikistan and Uzbekistan. A complete threat assessment was performed evaluating the short-term threats from overexploitation, overgrazing, landslides, and fragmentation as well as long-term threats from climate change. Based on key indicators of genetic diversity and threat magnitude, we developed an approach to identify wild populations for priority conservation and defined appropriate measures to conserve their genetic diversity based on the specific threat magnitudes. We propose (i) ex-situ conservation in areas with ‘severe threat level’ due to climate change and (ii) in-situ conservation in areas with ‘minor threat level’ due to climate change. In addition, we suggest (iii) assisted natural regeneration in areas where ‘minor threat levels’ from climate change coincide with ‘severe threat levels’ from one or more short-term threats. Our research shows high levels of genetic diversity as well as high threat levels in the walnut populations examined across three countries. Overgrazing and overexploitation were identified as the two most important threats whereas climate changed turned out to be of minor concern in the near future. Four out of the five populations selected for priority conservation are severely threatened: Kara-Alma (KGP3) and Sariosiyo (UZP4) by overexploitation and overgrazing, Vanj (TJP2) by landslides and fragmentation and Bostanlyk_2 (UZP2) by overexploitation. Only the Baljuvon population (TJP4) in Tajikistan shows minor threat levels in the short and long term. Thus, for all five priority populations the most appropriate conservation approach appears to be in-situ conservation. Spontaneous natural regeneration should be sufficient to ensure the long-term survival of the Baljuvon population (TJP4), while for the other four priority populations assisted natural regeneration may be needed. This network of five sites represents the minimum number of conservation areas for wild walnut in the three countries that should be established to capture a significant amount of the species genetic diversity. Conservation efforts could be extended to home gardens, which are a valuable genetic reservoir for the wild diversity found in the region.